Acúmulo de micronutrientes em materiais genéticos de cafeeiro Conilon - Venancio, Felipe Cassa Duarte (2016)
In order to characterize the accumulation of micronutrients (Cu, Zn, Mn, Fe and B) of dry matter and verify the variation in the content of these elements in genetic material of Conilon coffee, a study was carried out using the following genetic materials